Comparative study on atomic layer deposition of HfO2via substitution of ligand structure with cyclopentadiene. Issue 4 (19th December 2019) - Park, Sungmin; Park, Bo-Eun; Yoon, Hwi; Lee, Sanghun; Nam, Taewook; Cheon, Taehoon; Kim, Soo-Hyun; Cheon, Hwansung; Im, Sangkyun; Seong, Taegeun; Kim, Hyungjun
Abstract : Theoretical and experimental studies were investigated on the growth characteristics and electrical properties of HfO2 films using Hf(N(CH3 )2 )4 and CpHf(N(CH3 )2 )3 . Abstract : With the scaling down of complementary metal–oxide semiconductors (CMOS), atomic layer deposition of high-quality HfO2 has emerged as a key technology for ultrathin and high- k gate dielectrics. Recently, heteroleptic ligand structures have been introduced to complement the limitations of existing homoleptic precursors. Among the heteroleptic precursors, partial substitution with cyclopentadiene (Cp)-based ligands has been employed for controlling the volatility and thermal stability of precursors. In this study, we investigated the effects of the Cp ligand on the high- k properties of ALD HfO2 by comparing Hf(N(CH3 )2 )4 and CpHf(N(CH3 )2 )3 through theoretical and experimental methods. We theoretically predicted the changes in precursor behavior on the surface due to the Cp ligand, such as the high activation energy for the final chemisorption and the steric hindrance caused by the bulky Cp ligand. Additionally, we experimentally found that these changes affect not only the growth rate of ALD HfO2 but also the film properties. The Cp ligand on the surface sterically hinders the reaction of the nearby OH group with precursor molecules, retaining the residual OH content in the films. Consequently, the high OH content in the films degrades the film density and leakage current of ALD HfO2 as a high- k film.